2014
DOI: 10.1371/journal.pone.0093071
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between Body Mass Index and Health-Related Quality of Life

Abstract: ObjectiveHealth-related quality of life (HRQoL) is an important outcome in individuals with a high risk for cardiovascular diseases. We investigated the association of HRQoL and body mass index (BMI) as an indicator for obesity.DesignSecondary longitudinal analysis of the ORBITAL study, an intervention study which included high-risk cardiovascular primary care patients with hypercholesterolemia and an indication for statin therapy.MethodsHRQoL was determined with the generic Short Form (SF)-12 health status in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…Regarding the association between BMI and HRQoL, the findings in this study were in line with an England study that there was a significant association between BMI and HRQoL in the general population [103]. The findings in this study were not in agreement with inverse association between BMI and self-reported physical HRQoL [104], inverse association between BMI and physical HRQoL and positive association between BMI and mental HRQoL [105], inverse U-shaped association scores [106], and complex association [107]. Regarding the association between smoking and HRQoL, the findings in this study were not in agreement with inverse association [108][109][110][111][112].…”
Section: Discussionsupporting
confidence: 51%
“…Regarding the association between BMI and HRQoL, the findings in this study were in line with an England study that there was a significant association between BMI and HRQoL in the general population [103]. The findings in this study were not in agreement with inverse association between BMI and self-reported physical HRQoL [104], inverse association between BMI and physical HRQoL and positive association between BMI and mental HRQoL [105], inverse U-shaped association scores [106], and complex association [107]. Regarding the association between smoking and HRQoL, the findings in this study were not in agreement with inverse association [108][109][110][111][112].…”
Section: Discussionsupporting
confidence: 51%
“…Covariates included age, sex, body mass index (BMI), waist circumference (WC), education, income, residence, exercise, marital status, smoking status, comorbidity of chronic disease, and KL grade. They were the significant determinants (p value < 0.05) for poor HRQOL in univariate logistic regression analysis (data not shown) or clinically important variables on poor HRQOL identified in previous studies [ 26 ].…”
Section: Methodsmentioning
confidence: 76%
“…This was true for the PCS where differences were found in age and gender, but also in BMI. The latter is known to be associated with a decreased QoL among the general population . Reassuringly, the PCS was not affected by a decreased eGFR < 60 ml/min/1.73 m 2 , which is known to decrease physical functioning .…”
Section: Discussionmentioning
confidence: 89%